The value of creative activities in the recreational field: the grounded theory perspective - Lisauskienė, Dovilė; Leščinskij, Robert (Creativity Studies, 2025)
The current article employs a constructivist grounded theory approach to analyze the relationship between recreation and creativity. Researchers explore how engaging in imaginative recreational activities foster and sustain social connections, emphasizing the importance of social settings and interactions. In the context of recreation, creativity is highlighted as a crucial process enriched with educational and developmental elements, characterized by originality and usefulness. The value of creative activities is particularly stressed, noting their ability to transform emotions, replace negative feelings with positive ones, and enhance self-confidence among young people. This self-confidence serves as a medium for socialization and self-development. Additionally, the role of communication is emphasized, as creative activities provide youth with opportunities to communicate and build social ties.